Performance of Catching of Tuna, Cakalang, Tongkol (TCT) in Sea South East Java as a Basis for Management of Large Pelagic Fish Resources - Harahab, Nuddin; Abidin, Zainal; Tiarantika, Reny (Jurnal Pembangunan dan Alam Lestari, 2022)
The southern waters of East Java are included in the fisheries management area (WPPNRI) 573 and are known to have abundant potential resources of Tuna, Cakalang, and Tongkol (TCT); TCT fish have important economic value and are spread in almost all regions in Indonesian waters. The need and high market demand for these fish causes the intensity of fishing to increase. This study aimed to examine fish catch performance in the last 10 years. This study uses primary and secondary data. Primary data was obtained through field survey methods, observations, and interviews with 45 respondents. Secondary data were obtained from BPS and reports from the fisheries service within the last 10 years. The results showed that TCT capture fisheries in East Java, especially in Malang and Trenggalek districts, experienced a decline in catch performance. This is because the amount of fishery production and the biological size of fish have decreased in the last 10 years. Keywords: Capture Fisheries, Production Performance, TCT